(untitled) - O'Brien, Liz (New York, 2013)
Through Speak Well's listener-centered approach to public speaking, one in which the speaker engages in a vibrant conversation with listeners rather than giving a static performance, students learn that their primary purpose as speakers is to communicate ideas. The result is reduced student anxiety about speech delivery, increased self-assurance, and more authentic, successful speeches.
Keywords: Nói trước công chúng,Public speaking